Aesthetics and the Imitation of Antiquity in Early Gothic Sculpture - Terrier Aliferis, Laurence (Turnhout: Brepols, 2022)
This article discusses the emergence of a style, known as the ‘1200 style’, one of whose principal characteristics is the evocation of antique art. Examination of the stylistic evolution of early Gothic sculpture similarly reveals a concern for realistic representation in the late twelfth and early thirteenth centuries. Sculptors, like goldsmiths, tried to create convincing figures whose proportions and anatomies are consistent with those found in nature. Related to the development of the 1200 style and its links with antique work, the objective of these sculptors was not Antiquity itself but an aesthetic of naturalism. The Latin and French texts of the same period make abundant use of the antique topos of the statue animated by the breath of life. The realistic tendencies of artistic production are here explained by a desire to give presence to divinity through sculpture with a powerful capacity for re-presentation.
Keywords: Gothic Sculpture; Reception of Antiquity; 1200 Style